Improvement of the adhesive bonding properties of an polyamide 6 injection molded fiber reinforced plastic component by laser beam pre-treatment. (November 2021) - Weiland, Josef; Dittmar, Hagen; Beier, Christoph JA; Ramesh, Chiranth; Marx, Bernd; Schiebahn, Alexander; Jaeschke, Peter; Overmeyer, Ludger; Reisgen, Uwe
Fiber-reinforced plastics (FRP) are widely used in the automotive industry due to their lightweight construction potential. Especially, injection-molded components are very popular because of their short cycle times. Unfortunately, this manufacturing process results in some disadvantages for delayed adhesive bonding. On the one hand, such thermoplastics have a very low surface energy (Polyamide 6 (PA6) 36 mJ/m), on the other hand residues of release agents on the surface hinder adhesion between product and adhesive. These disadvantages have to be overcome by the right surface pre-treatment process. Currently, a solvent-containing process is usually used for this purpose. If necessary, the use of primer is common. In the presented paper, the pre-treatment process of an injection-molded component made of polyamide 6 reinforced with glass short-fibers is presented. First, material-specific properties are measured. The influence of laser pre-treatment at 355 nm and 1064 nm wavelength is investigated. Measurements of surface free energy and surface roughness are conducted. The bonding strength is validated by peel test and tensile shear tests. The shear strength was doubled by laser pre-treatment at a medium energy level, partially cohesive failure of the adhesive was achieved. Both investigated wavelengths led to a great improvement of bonding strength at suitable parameters.